Determinants of internal migration in Kazakhstan - Alisher Aldashev; Barbara Dietz (Osteuropa-Institut Regensburg, 2011)
In this paper we analyze the determinants of interregional migration in Kazakhstan using quarterly panel data on region to region migration in 2008-2010. To the best of our knowledge this is the first study on interregional population flows in Central Asia. We find that migration is determined by economic factors, first of all income: People are more likely to leave regions where incomes are low and more likely to move to regions with a higher income level. Furthermore, mobility is larger between more populated regions. Distance has a strong negative impact on migration, indicating high migration related costs and risks. Assuming that high migration costs are caused by poor infrastructure, investments in public and social infrastructure should facilitate regional income convergence in Kazakhstan and improve living standards in depressed regions.
Keywords: J61; P36; R23; 330; Interregional migration; Kazakhstan; Gravity model; Binnenwanderung; Gravitationsmodell; Schätzung; Kasachstan